Facts and values in Health Technology Assessment: the objectives of ethical analysis in the evaluation processes of health technologies - Refolo, Pietro; Sacchini, Dario; Raimondi, Costanza; Spagnolo, Antonio G. (Medicina e Morale, 2024)
In light of the role that the ethical domain will soon assume according to the “format” established by the European Regulation on Health Technology Assessment (HTA) (2021/2282), this article aims to further specify the objectives and significance of ethical evaluation in HTA. Drawing on the results of a European project in which the authors participated, namely VALIDATE-HTA (VAlues in Doing Assessments of healthcare Technologies), and based on a case study on the use of cochlear implants for children born deaf who have never naturally acquired spoken language (prelingually deaf children), the article will argue, in particular, for the impossibility of conceiving HTA without reference to values. It will demonstrate how their separation would lead the discipline to provide correct answers to poorly formulated questions, ultimately resulting in its irrelevance.